A beneficial arthropod dataset for agricultural landscapes in Western Canada, and adjacent mountain ecosystems - Abigail L. Cohen; Lincoln R. Best; Danielle Clake; Diane Edwards; Michael Gavin; Sarah A. Johnson; Jennifer Retzlaff; Samuel V. J. Robinson; Jess Vickruck; Paul Galpern (Scientific Data)
Abstract One of the largest drivers of global biodiversity trends is land use change and habitat loss. Through several studies of beneficial arthropods, we have compiled a spatially extensive passive-sampling arthropod dataset for Western Canada focused on landscape diversity. This dataset, collected from 2015–2019, consists of more than 200,000 specimens, five arthropod orders, and 26 families of either pollinators (Hymenoptera, Diptera) or natural enemies of pests (Coleoptera, Araneae, Opiliones). In the research that collectively makes up this dataset, there are 409 sampling sites in two focal areas: the Canadian Rockies (n = 70) and the agriculturally intense Canadian prairies (n = 339). Sampling in the montane region focused on Bombus species, while both pollinators and natural enemies were sampled in the prairies. Within the prairie region, there was also a focus on non-crop habitat that occurs within or adjacent to the annual crop fields and rangelands that dominate the region. This data can be used to investigate beneficial insect abundance and richness over a gradient of elevation, land cover, landscape diversity and climate.